The impact of legalization of access to recreational Cannabis on Canadian medical users with Cancer - Philippa Hawley; Monica Gobbo; Narsis Afghari (BMC, 2020)
Abstract Background Canada legalized cannabis use for medical purposes in 1999. Legalization of cannabis for recreational purposes in October 2018 offered the opportunity to assess the impact of recreational legalization on cancer patients' patterns of use to identify learning points that could be helpful to other countries considering similar legislation. Method Two identical anonymous cross-sectional surveys were administered to cancer patients in British Columbia 2 months before and 3 months following legalization, with the same eligibility criteria. The prevalence of medical cannabis use, the distribution of symptoms leading to use, the most common types of cannabis products and sources, reasons for stopping using cannabis, and barriers to access were assessed. Results The overall response rate was 27%. Both cohorts were similar regarding age (median = 66 yrs), gender (53% female), and education (approximately 85% of participants had an education level of high school graduation and higher). Respondents had multiple motives for taking cannabis, including to manage multiple symptoms, to treat cancer, and for recreational reasons. The majority of patients in both surveys did not use the legal medical access system. Comparison of the two cohorts showed that after legalization the prevalence of current cannabis use increased by 26% (23·1% to 29·1%, p-value 0·01), including an increased disclosure of recreational motive for use, from 32 to 40%. However, in the post-legalization cohort more Current Users reported problems getting cannabis (18%) than the pre-legalization cohort (8%), (p-value < 0·01). The most common barrier cited was lack of available preferred products, including edibles, as these were only available from illegal dispensaries. Conclusions Results showed that legalization of cannabis for recreational purposes may have an impact on those who use medical cannabis. Impacts include an increase in prevalence of use; problems accessing preferred products legally; higher cost, and difficulties using a legal access system. The desired goal of regulation in reducing harms from use of illegal cannabis products are unlikely to be achieved if the legal process is less attractive to patients than use of illegal sources.